Modeling CaMKII-mediated regulation of L-type Ca2+ channels and ryanodine receptors in the heart - Greenstein, Joseph L.; Foteinou, Panagiota T.; Hashambhoy-Ramsay, Yasmin L.; Winslow, Raimond L. (Frontiers in Pharmacology, 2014)
Excitation-contraction coupling (ECC) in the cardiac myocyte is mediated by a number of highly integrated mechanisms of intracellular Ca2+ transport. Voltage- and Ca2+-dependent L-type Ca2+ channels (LCCs) allow for Ca2+ entry into the myocyte, which then binds to nearby ryanodine receptors (RyRs) and triggers Ca2+ release from the sarcoplasmic reticulum in a process known as Ca2+-induced Ca2+ release. The highly coordinated Ca2+-mediated interaction between LCCs and RyRs is further regulated by the cardiac isoform of the Ca2+/calmodulin-dependent protein kinase (CaMKII). Because CaMKII targets and modulates the function of many ECC proteins, elucidation of its role in ECC and integrative cellular function is challenging and much insight has been gained through the use of detailed computational models. Multiscale models that can both reconstruct the detailed nature of local signaling events within the cardiac dyad and predict their functional consequences at the level of the whole cell have played an important role in advancing our understanding of CaMKII function in ECC. Here, we review experimentally based models of CaMKII function with a focus on LCC and RyR regulation, and the mechanistic insights that have been gained through their application.